Factor Analysis of Smart Social Media Technology to Promote Professional Learning Communities for Teachers - Mingsiritham, Kemmanat; Chanyawudhiwan, Gan; Paiwithayasiritham, Chaiyos (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This research aimed to study factor analysis of smart social media technology to promote professional learning communities for teachers.   The sample included 900 teachers in basic education, selected by Simple   Random Sampling method. The sample group was divided for exploratory   factor analysis (EFA) and confirmatory factor analysis (CFA), 450 each. Research tool was a questionnaire with 5 levels of rating scale. Data were analyzed by exploratory factor analysis and confirmatory factor analysis. The results of the study revealed that: 1. Exploratory factor analysis of smart social media technology to promote professional learning communities for teachers consisted of 7 components: 1) professional learning communities for teacher, 2) cloud technology, 3) augmented reality, 4) internet of thing, 5) social  technology, 6) data analytics technology, and 7) mobile technology and 2. Confirmatory factor analysis of smart social media technology to promote  professional learning communities for teachers (SMPLC) found that the model was consistent with the empirical data ( =6.17, df=6, p=0.405).